TEACHER’S STRATEGIES IN TEACHING WRITING DESCRIPTIVE TEXT AT SNIOR HIGH SCHOOL - Sintha Veronika Sianturi; Masitowarni Siregar; Johannes Jefria Gultom (Universitas Negeri Medan, 2024)
This research aimed to describe the teacher’s strategies in teaching writing descriptive text and to describe the problems faced by the teacher. It was a descriptive qualitative research design. The subject of this research was one English teacher of SMA Swasta RK Serdang Murni Lubuk Pakam. The data of this research were the teacher’s language and the activities in teaching writing descriptive. The results showed that the teacher applied seven strategies they were (1) modify comprehensible input, (2) make lesson visual, (3) link new information, (4) determine key concepts, (5) modify vocabulary instruction, (6) use cooperative learning strategies, and (7) modify testing. And the problems faced by the teacher were the lack of students’ vocabularies and the participation in group work.